2014
DOI: 10.1136/vr.102119
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between metabolite and IGF1 concentrations with fertility and production outcomes following left abomasal displacement

Abstract: Left displacement of the abomasum (LDA) is an important periparturient disorder of dairy cows. This study evaluated differences in metabolic parameters between case-control pairs of cows (n=67) from 24 farms, and related these to outcomes in fertility and production. Cows with an assisted delivery were ×3 more likely to develop LDA, and affected cows tended to have had a longer dry period. At recruitment, cows with LDA tended to be in lower body condition accompanied by significantly higher circulating concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
3
13
0
1
Order By: Relevance
“…The findings of Lyons and others (2014) support this, as well as reporting an associated mean milk production loss of 2272 litres per LDA case compared with matched controls.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The findings of Lyons and others (2014) support this, as well as reporting an associated mean milk production loss of 2272 litres per LDA case compared with matched controls.…”
supporting
confidence: 64%
“…A previous study indicated that higher than normal serum levels of non-esterified fatty acid (NEFA) and β-hydroxybutyrate (BHB), as well as decreased calcium concentrations, contribute to increased culling risk in the first 60 days after calving (Chapinal and others 2012). Lyons and others (2014) looked at the effects on productivity, fertility and risk factors for culling associated with cows experiencing LDA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the odds of culling within 60 d of surgery were 13 times greater in cows with dystocia which later developed an LDA compared with cows without a difficult calving. Interestingly, Lyons et al (2014) found that cows that had an assisted calving tended to be more likely to develop LDA, but that there were no differences in culling between the cows with LDA their paired controls. The increased odds of culling for nonketotic cows is supported by Croushore et al (2013), which indicated that cows with blood BHBA <1.2 mmol/L at the time of LDA corrective surgery were 2.5 times more likely to be removed from the herd within 30 d compared with cows with blood BHBA levels ≥1.2 mmol/L, similar to our results.…”
Section: Discussionmentioning
confidence: 97%
“…The circulating IGF1 concentration at this time correlates positively to the dry matter intake, BCS, and circulating insulin concentrations, and negatively with NEFA and BHB (Wathes et al 2007). Recently, a study has been showed that a low concentration of IGF1 in the peripartum period is an indicator for LDA in addition to elevated BHB and NEFA concentrations (Lyons et al 2014). IGF1 concentrations in postpartum cows change gradually rather than abruptly support the idea that lower IGF1 concentrations are likely to precede the development of LDA.…”
Section: Metabolic Indicatorsmentioning
confidence: 81%